Sets of Subspaces of a Projective Plane PG(2,q) Over Galois Field GF(q) - Mahammad, M. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this thesis, some sets of subspaces of projective plane PG(2,q) over Galois field GF(q) and the relations between them by some theorems and examples can be shown.